Affective and predatory violence: from evolutionary adaptation to psychiatric morbidity - Meloy, J. Reid (Frontiers in Psychiatry, 2025)
Nearly a century of mammalian research has supported the bimodal nature of violence. Predatory (instrumental) violence finds its evolutionary origins in hunting, while affective (reactive, impulsive) violence originates in the need to defend against an imminent threat. Both modes of violence serve survival, and none of us would be here if our ancestors did not excel at both. The capacity for both affective and predatory violence is neurobiologically atavistic, but contemporary society controls its expression through social learning, cultural guardrails and legal sanctions. Psychiatry and other mental health professions, however, often confront both affective and predatory violence in the context of psychiatric and personality disorders; and specifically, in their roles as threat assessors or forensic evaluators. This perspective underscores the importance of discerning extremely violent events as either affective or predatory, and details the criteria for doing so.